Design of Student Worksheet Development Based on the Jigsaw Cooperative Learning Model - Kurniawan, Sigit; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
Collaboration skills are one of the skills that are built in 21st-century education. With collaborative skills, students are expected to be able to work together with each other to help and complete to carry out certain tasks in order to obtain a predetermined goal. The jigsaw cooperative learning model as one of the means in building collaboration skills requires the adequacy of teaching materials. This study aims to produce products in the form of Student Worksheets (LKS) that fit the jigsaw cooperative learning model. This study uses the Design Research type Development Study development model. The research subjects were students of class X Muhammadiyah Cangkringan Sleman Yogyakarta. The stages in this study were researchers designing prototype 1. The results of prototype 1 were tested one-to-one, parallel to the expert review stage, as the basis for revision to improve and produce a prototype 2. Prototype 2 was tested in the small group as a basis for revision to improve and produce prototypes 3. The results of this study are prototypes 2 which are ready to be used at the small group stage.